Práticas pedagógicas em salas multisseriadas - Amorim, Francilene Lopes de (Universidade Federal do Tocantins, 2020)
The present research aims to verify how pedagogical practices are developed in two multiserial classes, of the Manoel de Sousa Lima Municipal School located in the Folha Grossa community, rural area of the municipality of Tocantinópolis-TO. Based on Freire (1986), the conception of pedagogical practice is assisted by the term dialogical,in which the construction of knowledge is seen as a process carried out by both actors: teacher and student, in the direction of a critical reading of reality. As a problem of the research, the following question is used: how does the process of organization and implementation of pedagogical practices occur at the Manoel de Sousa Lima Municipal School? The research is characterized as being of the case study type, qualitative approach and exploratory nature, as well as bibliographic and documentary review.As a data collection technique, interviews were conducted with two teachers and the principal of this school. Among the results found about pedagogical practice in the two classes studied, it is found that it is traditional model. In this perspective, pedagogical practices are elaborated, mainly, in a traditional way, in which teachers work with the support of urbanized textbooks that have little to do with the reality of the community and multiserialized teaching. Teachers find it difficult to perform their classes, among which, the absence of the active relationship between family and school and the lack of training for multiserial education. Another result found refers to the relationship that is established between teacher and student, being possible toperceive there is a good relationship, however, what makes it difficult to are the strategies used to make classes more successful in their execution and achieve the goal Desired. Finally, research can contribute reflections in the context of teaching pedagogical practice in the context of multiserial teaching.